2019
DOI: 10.1056/nejmoa1803731
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Mismatch at LIMS1 Locus and Kidney Allograft Rejection

Abstract: BACKGROUND In the context of kidney transplantation, genomic incompatibilities between donor and recipient may lead to allosensitization against new antigens. We hypothesized that recessive inheritance of gene-disrupting variants may represent a risk factor for allograft rejection. METHODS We performed a two-stage genetic association study of kidney allograft rejection. In the first stage, we performed a recessive association screen of 50 common gene-intersecting deletion polymorphisms in a cohort of kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 38 publications
8
107
0
Order By: Relevance
“…However, recent findings opened up a new prospect in this field; the genomic collision may be a relevant underlying mechanism to consider in such cases. 15 Infection rate was 42% in the present study. Hwang et al also reported high rate of infection complications in ABOi kidney transplantation recipients (66%).…”
Section: Discussionsupporting
confidence: 48%
“…However, recent findings opened up a new prospect in this field; the genomic collision may be a relevant underlying mechanism to consider in such cases. 15 Infection rate was 42% in the present study. Hwang et al also reported high rate of infection complications in ABOi kidney transplantation recipients (66%).…”
Section: Discussionsupporting
confidence: 48%
“…22 Both IFNɣ and TNFα accentuate antibody-mediated injury in AMR. [23][24][25] Moreover, tubular proteins can be targeted by non-HLA antibodies, 22,26 which reinforces the rationale for studying AMR in the tubulointerstitium.…”
Section: Introductionmentioning
confidence: 70%
“…We also found an anti-LIM zinc finger domain containing 1 (LMS1) autoAb among INSIP-associated natural autoAbs. Recently, a genomic mismatch in the LIMS1 gene was identified as a cause of previously unpredictable rejection [44]. In this previous study, production of IgG2-and IgG3-types of anti-LIMS autoAbs was associated with allograft rejection.…”
Section: Intracellular Antigens Extracellular or Membrane Antigensmentioning
confidence: 82%
“…LOXL2 [42,43], LIMS1 [44], NINJ2 [41], HVCN1 [45,46], TMEM79 [47], VSTM2A [48], FNDC4 [49] Interestingly, especially among antigens recognized by INSIP patient sera, there are many extracellular or membrane proteins, which are accessible by antibodies even under normal conditions. This suggests that the antigen-antibody interactions may be implicated in the pathogenesis or clinical course of disease.…”
Section: Intracellular Antigens Extracellular or Membrane Antigensmentioning
confidence: 99%